UPAYA PENCEGAHAN STUNTING MELALUI EDUKASI ASI EKSKLUSIF DAN TEKNIK MENYUSUI TAHUN 2025 - Sofia, Norlaila; Prihatanti, Nur Rohmah; Aprilea, Noor Adha (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
One of the main efforts in preventing stunting is through exclusive breastfeeding. To support this, health education and breastfeeding technique training are carried out to the community in the work area of the Astambul Health Center. The target of this activity is breastfeeding mothers with children aged 0–24 months. The activity partner, namely the Astambul Health Center, faces a high prevalence of stunting, so a strategy is needed to accelerate stunting reduction through health education on family empowerment, the Healthy Living Community Movement (Germas), and the optimization of the First 1000 Days of Life (HPK), especially related to exclusive breastfeeding and correct breastfeeding techniques. This activity was attended by 20 breastfeeding mothers. As part of the training, participants practiced proper breastfeeding techniques with the assistance of facilitators. The evaluation was carried out in two stages: (1) immediately after counseling to assess participants' understanding of exclusive breastfeeding and correct breastfeeding techniques; and (2) one month after the activity to evaluate the success of the application of the technique in daily breastfeeding practice. The results of the evaluation showed an increase in the knowledge and skills of the participants, which is expected to support efforts to reduce the stunting rate in the region through more optimal breastfeeding practices during the 1000 HPK period.